EFFECT OF SETTING OF ETCS ON BOARD UNIT ON BRAKING CURVE (Perner's Contacts, 2016)
The paper follows on previous author’s paper about effects of ETCS on braking curves. In this paper are compared two Baselines (2 and 3) from the angle of set-up of OBU. There are some parameters which are different and they have influence of the braking curve. The simulation of those parameters has been done and results are presented in this paper.
Keywords: ETCS; OBU (on-board Unit); braking curve